High-Resolution musculoskeletal ultrasound in India: The present perspective and the future - Raghav Aggarwal; Vishal Kaura Aggarwal (Indian Journal of Rheumatology)
High-resolution musculoskeletal ultrasound (HRMSK US) has evolved tremendously from being performed in dark lit scanning rooms to being done at a remote setting, being one of its kind of modalities where live streaming is making remote diagnosis possible; like self-scanning by an astronaut in outer space, or, an on field assessment of an acute injury in a high-stake football match , or a hand-held device used for scanning at a remote location, with the images streamed over the net for interpretation. It began as gray scale imaging; however, as power Doppler came into practice, it gave a leap to the use of ultrasound in inflammatory arthritis. Three-dimensional power Doppler, beam steering, sonoelastography, contrast ultrasound, and fusion imaging are the new weapons in the armamentarium of MSK US. The role of MSK US ranges from detecting various changes in rheumatological diseases; be it active synovitis, bony erosions, enthesitis, assessment of crystal deposition, salivary gland changes, and vessel changes, aiding in diagnosis, especially in children. HRMSK US has an established role as a diagnostic tool, both as a primary modality and as an adjunct to other modalities in orthopedic practice and sports medicine also, and has evolved as a primary therapeutic tool in these fields, be it pinpoint-guided steroid injections, platelet-rich plasma injections, and barbotage of calcium deposition in situations such as calcific tendinitis. Even with all these advantages, it is still sparingly used in the practice of rheumatology in India. The authors believe that it is likely to be more widely used in the future given the enormous scope of its applications.